Photodermatitis in a bottle-fed baby due to a liquid preparation for domestic sterilization. - Cutrone, M.; Beneforti, M. (European Journal of Pediatric Dermatology, 1997)
A 4-month-old baby girl presented an irritant contact photodermatitis, caused by the application of a liquid containing bergamot perfume, which was followed by sun exposure. This is probably the first case reported in the literature of irritant contact photodermatitis caused by a sterilizing liquid for pacifiers, which contains bergamot in order to mask the bad smell of hypochlorite. The Authors disapprove the usage of photosensitizers in products which are largely used in childhood. This is particularly true in the actual era, which is characterized by a particular attention of the mass media to the problem of sunburns.